Low-cost transmit-array antenna prototype at Ka-band combining low profile and mechanical wide-angle beam scanning - Matos, S. A.; Costa, J. R.; Felício, J.; Fonseca, N. J. G.; Vaquero, Á. F.; Arrebola, M.; Fernandes, C. A. (2023 International Workshop on Antenna Technology (iWAT), 2023)
Transmit-arrays (T As) have been proposed as a cost-effective technology for designing beam antennas capable achieving wide-angle beam steering using only in-plane mechanical movements. As a spatially fed antenna, its performance is limited by the system focal distance. The design requires a rather complex trade-off angle between maximum scanning angle, minimum focal distance and minimum gain considering all beam pointing directions. The authors developed a new iterative method for optimizing the TA phase correction for extremely low focal distances (F/D<0.4). Herein, this general procedure is validated through a prototype comprised of an open waveguide, as a primary source, and a fully dielectric 3D- printed T A. The rectangular aperture dimensions are 195x145x16 mm and the focal source is placed at 50 mm (F/D~0.34). This antenna scans up to 50°, with a gain of 25 dBi at 30 GHz, 1.5 dB of scan loss, SLL< -10 dB and 1 dB-bandwidth of 6.7 % (29 to 31 GHz).